Nineteenth Century Accounting Error - Brief, Richard P. (Journal of Accounting Research, 1965)
Only fleeting attention has been given to the possibility of persistent error or bias in the calculations on which investment, output, and/or pricing decisions were based in the nineteenth century. This is an indirect tribute to the influence of Max Weber and other rationalists who stressed the concept of a rational capitalistic establishment employs capital accounting, that is, an establishment which determines its income yielding power by calculation according to methods of modern bookkeeping and the striking of a balance. 1 Schumpeter's views are even more exalting.